HUBUNGAN PENGETAHUAN DAN SIKAP PETUGAS CLEANING SERVICE TERHADAP PENCEGAHAN HEALTHCARE- ASSOCIATED INFECTIONS (HAIs) - Hendra " Saputra; Darwin " Karim; Herlina " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractHealthcare-Associated Infections (HAIs) are infections that occur in hospitals or in the health care system that are derived from the deployment process in health care resources, either through patient and health workers, visitors and other sources. The infections happened with several kinds of disease agents can be bacteria, viruses, fungi, parasites which are pathogenic microbes that cause of diseases. The aims of study to know the correlation between knowledge and attitude ofcleaning service employees toward prevention from Healthcare-Associated Infections (HAIs). The study employed the descriptive correlation design focus on cross sectional approach. The samples of study were 7 respondents. It carried out based on the inclussion criteria with accidential sampling technique. The instrument of study is questionnaires as measurement that was made by researchers. Questionnaires for both variables have been tested the validity and reliability. The finding of this study showed the Chi Square is p value 0,444 > α (0,05) and it could be seen there was no correlation significant between knowledge and attitude of employees cleaning service toward prevention from Healthcare-Associated Infections (HAIs). The results of this study are expected to cleaning service employees can improve the prevention of Healthcare-Associated Infections (HAIs). Key Words: Knowledge, Attitude, Prevention Healthcare-Associated Infections (HAIs).